Principal Educator Management on Strengthening the 21st Century Skills of Elementary School Teachers: A Systematic Literature Review - Intifada, Aljazira Yasyirulgaza; Marmoah, Sri; Duca, Diana Sinziana (Universitas Sebelas Maret, 2026)
21st century skills are a fundamental demand for teachers to have in facing the demands of modern education in which there are critical thinking, communication, collaboration, and creativity. The purpose of this research is to analyze how the role of educator management and principals in developing 21st century skills of teachers in primary schools. The research method used is Systematic Literature Review (SLR) by systematically analyzing scientific articles in accordance with the field studied in this study. The study was carried out through the identification of sources, selection of the criteria studied, and analysis of the content of the selected research findings. The results of the study show that it shows that the management of school principal educators plays a strategic role in strengthening teachers' 21st century skills through the implementation of management functions which include planning professional development programs, organizing collaborative activities for teachers, implementing academic supervision oriented to 21st century learning, and continuous supervision and evaluation. In addition, principals who apply participatory, communicative, and visionary leadership styles are able to build a pattern of teachers' professional interaction that supports the development of communication skills, collaboration, and adaptation to change. The conclusion of this study confirms that planned and collaborative management of school principal educators is a key factor in strengthening teachers' 21st century skills and improving the quality of education in elementary schools.